Constraining long‐term fault activity in the brittle domain through in situ dating of hydrothermal monazite. (6th November 2018) - Bergemann, Christian A.; Gnos, Edwin; Berger, Alfons; Whitehouse, Martin J.; Mullis, Josef; Walter, Franz; Bojar, Hans‐Peter
Abstract: SIMS Th–Pb dating of hydrothermal fissure‐vein monazite‐(Ce) has the unique potential to date multiple tectonic events under low‐grade metamorphic brittle/ductile conditions over large time frames. Monazites‐(Ce) from brittle fault systems in the Eastern Alps allow us to constrain their Cretaceous activity over 20 Ma within single crystals, recording all major tectonic events. Eo‐Alpine formation of the fluid‐filled fissure‐veins occurred 90 Ma ago at 352 ± 19°C and 342 ± 42 MPa. This corresponds to peak conditions during regional metamorphism of the Cretaceous collisional nappe stacking. Several stages of dissolution–reprecipitation/recrystallization record fault activity between 84 and 70 Ma. Corresponding fluid inclusions indicate conditions of 229 ± 10°C and 143 ± 20 MPa. This correlates with the formation of sedimentary basins during post‐orogenic extension associated with strike‐slip movements. The results strengthen the hypothesis that many large fault systems in the Eastern Alps developed during the Cretaceous orogeny and became reactivated during Neogene Alpine tectonics.